2017
DOI: 10.2174/1381612823666170622110046
|View full text |Cite
|
Sign up to set email alerts
|

“Stress” is 80 Years Old: From Hans Selye Original Paper in 1936 to Recent Advances in GI Ulceration

Abstract: The first scientific publication on 'general adaption syndrome', or as we know today 'biologic stress' has been published in Nature in 1936 by the 29-year old Hans Selye. His results in that short publication that contained no references or illustrations, were based on experiments in rats that were exposed to severe insults/ stressors, but his idea about a 'nonspecific bodily response' originated from his observations of sick patients whom he had seen as a medical student and young clinician. Autopsy of stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 79 publications
0
24
0
3
Order By: Relevance
“…This demonstrates that T-lymphocytes are sensitive to stress hormone levels and their receptor activation. It is well-known that glucocorticoids induce thymic atrophy (Pazirandeh et al, 2002;Roggero et al, 2006) and apoptosis in circulating T-cells (Cidlowski et al, 1996), which is consistently observed in different models of stress (Szabo et al, 2017). The pattern of ozone-induced decrease and AD-mediated recovery of circulating leukocyte cell subpopulations suggests that endogenous levels of glucocorticoid hormones are sufficient to dynamically regulate the relative size of cytotoxic and helper Tcell pools.…”
Section: Discussionmentioning
confidence: 94%
“…This demonstrates that T-lymphocytes are sensitive to stress hormone levels and their receptor activation. It is well-known that glucocorticoids induce thymic atrophy (Pazirandeh et al, 2002;Roggero et al, 2006) and apoptosis in circulating T-cells (Cidlowski et al, 1996), which is consistently observed in different models of stress (Szabo et al, 2017). The pattern of ozone-induced decrease and AD-mediated recovery of circulating leukocyte cell subpopulations suggests that endogenous levels of glucocorticoid hormones are sufficient to dynamically regulate the relative size of cytotoxic and helper Tcell pools.…”
Section: Discussionmentioning
confidence: 94%
“…While living in an aerobic environment, cells are exposed to the phenomenon of oxidative stress. The concept of stress and the mechanisms of the response to it were first described in 1936 [1] and the term "oxidative stress" was developed in the book of the same title in 1985. It was defined as an imbalance between oxidants and antioxidants, in favor of oxidants, that leads to interference in the transmission of signals and in damage to cellular structures [2].…”
Section: Introductionmentioning
confidence: 99%
“…Since its description by Hans Seyle in 1952, stress has been extensively studied in various ways. Indeed, stress has many facets, including physical, chemical, biological, and psychological as recalled in a recent review ( Szabo et al, 2017 ). Various types of stressors have been described for psychological stress, including those of Sharpe and Lewis, such as performance, social threat, boredom, lack of control of a situation, bereavement, and physical threat ( Sharpe and Lewis, 1995 ).…”
Section: Pathophysiology Of Psychological Stressmentioning
confidence: 99%